2022
DOI: 10.1063/5.0098276
|View full text |Cite
|
Sign up to set email alerts
|

Properties of high entropy borides synthesized via microwave-induced plasma

Abstract: Microwave-induced plasma was used to anneal precursor powders containing five metal oxides with carbon and boron carbide as reducing agents, resulting in high entropy boride ceramics. Measurements of hardness, phase structure, and oxidation resistance were investigated. Plasma annealing for 45 min in the range of 1500–2000 °C led to the formation of predominantly single-phase (Hf, Zr, Ti, Ta, Mo)B2 or (Hf, Zr, Nb, Ta, Mo)B2 hexagonal structures characteristic of high entropy borides. Oxidation resistance for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Most multicomponent borides have heterogeneities consisting of B 4 C, graphite, (Zr/Hf)­O 2 , and segregates of unitary or mixed-phase borides. These heterogeneities emerge at grain boundaries and improve the structural properties relative to those of their single-phase counterparts. These impurities get impregnated during material synthesis, typically via mechanical alloying and sintering of metal oxides in the presence of B 4 C. Monitoring and precise control of the proportion of such impurities is challenging; hence, estimating the hardness of a pure single-phase material devoid of grain boundary segregations is difficult and requires optimal synthesis methods that minimize exposure to oxide and carbonaceous contents. ,, , A widely reported multicomponent boride (Hf 0.2 Zr 0.2 Ta 0.2 Nb 0.2 Ti 0.2 )­B 2 has been reported to possess hardness between 16.4 and 25.4 GPa from experimental measurements, ,,,,,, with its single phase chemistry assuming 16.4 and 20.9 GPa per the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most multicomponent borides have heterogeneities consisting of B 4 C, graphite, (Zr/Hf)­O 2 , and segregates of unitary or mixed-phase borides. These heterogeneities emerge at grain boundaries and improve the structural properties relative to those of their single-phase counterparts. These impurities get impregnated during material synthesis, typically via mechanical alloying and sintering of metal oxides in the presence of B 4 C. Monitoring and precise control of the proportion of such impurities is challenging; hence, estimating the hardness of a pure single-phase material devoid of grain boundary segregations is difficult and requires optimal synthesis methods that minimize exposure to oxide and carbonaceous contents. ,, , A widely reported multicomponent boride (Hf 0.2 Zr 0.2 Ta 0.2 Nb 0.2 Ti 0.2 )­B 2 has been reported to possess hardness between 16.4 and 25.4 GPa from experimental measurements, ,,,,,, with its single phase chemistry assuming 16.4 and 20.9 GPa per the literature.…”
Section: Resultsmentioning
confidence: 99%
“…While intrinsic hardening is influenced by the metal-to-boron ratio and the arrangement of boron atoms, extrinsic effects emerge at the microstructural scale and involve the grain size, number of crystallographic phases, as well as segregations present in the material. Multicomponent borides generally do not form a single phase (see Supporting Information) and are contaminated with impurities like oxides and B 4 C, promoting segregation at the grain boundaries and hence an increased hardness due to the foregoing extrinsic effects. In contrast, and notably so, we find that single-phase multicomponent borides have lower hardness than their precursor counterparts. , Here, we examine the fundamental mechanisms associated with the intrinsic factors for hardness reduction in multicomponent borides.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we benchmarked our experimental hardness measurements against theoretical values. The theoretical hardness for the HEBs under study has been computed to be approximately 33 GPa in our prior work [ 15 ], using a partial occupation method (POCC) of small 15-atom unit cells. Here, we performed additional DFT calculations using SQS structures of varying size and shape up to 150 atoms (see Figure 7 a).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the small addition of H 2 (in addition to argon) helped to stabilize and concentrate the sample near the sample. A microwave power of 1.3–1.5 kW and chamber pressure of 2.4 × 10 4 –3.3 × 10 4 Pa was used to rapidly heat up the pellet (70–100 °C/min in this system) to 2000 °C, as also described in our previous works [ 15 , 16 ]. The precursor pellets were MW-plasma annealed using either BCTR or BTR at 2000 °C for 1 h.…”
Section: Methodsmentioning
confidence: 99%
“…One of the options for improving the service characteristics of HEA is to saturate them with boron atoms. Various methods of HEA boriding are used: using nanosized borating powders [19,20], plasma borating [21], using laser technologies [22] and plasma spark sintering technologies [23], and many others.…”
Section: Introductionmentioning
confidence: 99%